Paintable Films from Chemically Exfoliated 2D Bismuth Telluride Nanosheets. (10th February 2015) - Carroll, Elaine; Buckley, Darragh; Collins, Gillian; Holmes, Justin D; Razeeb, Kafil M; O'Dwyer, Colm
Abstract : This work highlights a method whereby solvent exfoliation of Bi2 Te3 into solution-dispersible 2D nanosheets can form a practical thin film that can be distributed across a surface. Optimized exfoliated suspensions are also shown to form smooth, uniform blends when mixed with poly ethylene glycol and other polymers to produce a paintable Bi2 Te3 film that can be applied to surfaces using an innovative painting technique. Atomic force microscopy, transmission electron spectroscopy, Raman scattering spectroscopy and scanning electron spectroscopy are used to examine the structure of the 2D nanosheets and the Bi2 Te3 thin films. Electrical transport studies show that the films have conductive pathways over a range of surfaces and various structural formations, linking the conductivity to the percolating conduction through the nanosheet ensemble.